Now or Never: Environmental Protection under Hyperbolic Discounting - Ralph Winkler (Kiel Institute for the World Economy (IfW), 2009)
The author analyzes the optimal investment in environmental protection in a model of an infinite series of non-overlapping hyperbolically discounting agents. He shows that without a commitment mechanism society is eventually stuck in a situation where all agents prefer further investment in the long run, yet neither present nor future agents will actually ever invest. Such an outcome is not only unsatisfactory for each generation but may also be inefficient in a Pareto sense. The author's results are consistent with real world observations, and thus provide a new explanation for weak environmental policy performance.
Keywords: Q50; D90; Q58; 330; Environmental policy; environmental protection; hyperbolic discounting; Markov perfect equilibria; tme-inconsistency; Umweltschutz; Umweltpolitik; Zeitpräferenz; Zeitkonsistenz; Theorie